Dampak Covid 19 Terhadap Ekonomi dan Lingkungan di Bali - Shinta Enggar Maharani (Environmental Research Center (PPLH) of Udayana University, 2021)
The island of Bali as one of the tourism centers in Indonesia has felt the huge impact of Covid 19. The economy of Bali, which relies on tourism with natural and cultural beauty, has experienced a very drastic decline. Data shows that the number of foreign tourists to Bali in January 2021 has decreased as deep as 93.33%, compared to the record in December 2020 and when compared to January 2020, the number of foreign tourists to Bali was recorded to have decreased by almost 100%, namely -99.998% (BPS, 2021). This paper aims to determine the impact of Covid 19 on the economy of Bali, which relies on environmental and cultural sustainability-based tourism as a tourist attraction. This paper uses a literature review analysis related to the economic and environmental impacts in Bali caused by the Covid-19 pandemic. The impact of the Covid 19 pandemic on the economy of Bali which relies on environmental and cultural sustainability-based tourism as a tourist attraction is enormous. The economic downturn and the increase in the volume of Hazardous waste due to the pandemic are real problems to be faced, although environmental restoration will greatly benefit Bali's future sustainability